Análisis del contexto de una pyme colombiana orientado a la implementación de un sistema de gestión de la calidad (2016)
This paper explores the internal and external context issues of a Colombian SMEs services provider. The analysis starts from a brief description of the challenges that SMEs is facing in an emerging countries such as Colombia, and the role of the quality management models as a strategic decision to create competitive advantages. Subsequently, SWOT analysis is performed in order to ensure knowledge of the organization and its environment for the planning of a QMS. Finally, the analysis concludes with a discussion made from the potential of this type of diagnostics and the qualitative results obtained by the study case.